An efficient, compact and low-cost Dual Cylinder Hydrostatic Actuator (DCHA). Issue 2 (4th May 2018) - Wiens, Travis
Abstract: Pump-controlled systems are highly efficient alternatives to the high throttling losses of valve-controlled systems. Closed-circuit systems have been widely adopted for rotary loads, but the asymmetrical nature of linear actuators has limited their acceptance. Hydrostatic linear actuators typically are costly or complex, inefficient or exhibit low force density. This paper presents a Dual Cylinder Hydrostatic Actuator, which is highly efficient for both resistive and overrunning loads, uses commercially available low-cost components, and provides the same high force of a conventional system in a similarly sized system. A steady-state model is presented, along with an experimental validation on a small-scale apparatus. An analysis of a full-scale application is performed, including strategies for mitigation of energy losses.